PH measurements hydrous ethanol fuel - Atilio, N. C.; Fertonani, F. L. [UNESP]; De Oliveira, E. C. (IOP Publishing, 2023)
The pH is one of the quality parameters of hydrous ethanol fuel (HEF), being established by Brazilian standard ABNT NBR 10891 and by American standard ASTM D 6423. The present work aims to compare the measurement systems proposed by the standards for measuring pH in hydrous ethanol fuel and compare them with the pH range found from pH indicators, considered as a standard measurement. The results reveal that the pH values obtained by the different systems used are statistically different from each other and different from the range found by the indicators.